Evaluation of Maturity Level and Recommendations for Improvement of Software Testing Process Based on Test Maturity Model Integration (TMMi): A Case Study - Prastiti, Rizdiani Tri; Hidayanto, Achmad Nizar (Jurnal Komtika (Komputasi dan Informatika), 2023)
XYZ company as one of the companies that provides Over-The-Top (OTT) services has problems related to defects that pass into the production environment caused by an ineffective testing process. This has an impact on user satisfaction as indicated by various user complaints when using the application. It is necessary to evaluate the maturity level which shows the ability to perform software testing and what recommendations can be given to improve the software testing process. Test Maturity Model Integration (TMMi) as a model for improving the software testing process has been widely known to improve the testing process and positively impact product quality. XYZ company, which is looking to improve its software testing process, uses the TMMi model as a reference to determine the maturity level of the testing process and provide best practices for the testing process. The assessment was conducted using the TMMi Assessment Method Application Requirement (TAMAR) and information was collected using the Delphi method. The assessment is carried out in the process area at the maturity level of level 2 and produces a rating value of P (Partially Achieved) so that the maturity level of the XYZ company software testing process is level 1 (Initial). Recommendations are prepared based on specific practices in the Test Planning and Test Environment process areas that still have weaknesses that must be improved to reach maturity level 2 (Managed). The process of preparing recommendations is assisted by the Deming cycle which is then validated with stakeholders whether these recommendations can be implemented according to the needs of XYZ company to improve the testing process.